DISCURSO, PODER E VIRILIDADE DO SUJEITO-MULHER CAROLINA MARIA DE JESUS EM QUARTO DE DESPEJO - Bassani, Sandra Lucia Dimidiuk (2018)
The discursive production of the virility of Carolina Maria de Jesus, in the work Quarto de Despejo: diário de uma favelada (1960), thought in the power-knowledge plots, is the central focus of this research that is developed in the light of the French Speech Discourse Analysis, more precisely from the contributions of Michel Foucault incorporated in this field of knowledge. Thus, anchored in fundamental and foundational concepts of Foucauldian arche-genealogy – as a statement, speech, language, subject and history – is a theoretical framework that makes it possible to describe and interpret statements that, at the time they produce the virility of the protagonist, point to the exercises of power and resistance from the writing practice of the author understood as a weapon to fight against the submissions of women to the yoke of political power, patriarchal and racist. In the analyzes what stands out are the processes of subjectivation of a black woman, a poor woman, a favela, a paper collector, a single mother of three children from different countries, with very little schooling that, finally and paradoxically, becomes an important writer in the scene of Brazilian literature. Such a reinvention of its socio-historical conditions of existence came from reading the books and magazines that it found in the trash and the fact that it, fearlessly, with his writing, in his diary, have exposed details of the living conditions of people living on the margins of society; she made denunciations of the authorities' disregard for the conditions of a citizen's life, perpetuating their daily difficulties in search of survival and of satisfying the hunger of the stomach and the culture; she broke down barriers separating "the living room dumping room", revealing the power that reading, literature and writing have as an element of transformation in the processes of subjectivation. Because she was a virile woman, that is, a guy who was eager for knowledge and resistance, whose (contra) behaviors responded to the urgency of survival in an inhuman cultural, social and political context, she was able to leave the eviction room.